Noncardiac Surgical Procedures After Left Ventricular Assist Device Implantation. Issue 4 (July 2016) - Taghavi, Sharven; Jayarajan, Senthil N.; Ambur, Vishnu; Mangi, Abeel A.; Chan, Elaine; Dauer, Elizabeth; Sjoholm, Lars O.; Pathak, Abhijit; Santora, Thomas A.; Goldberg, Amy J.; Rappold, Joseph F.
Abstract : As left ventricular assist devices (LVADs) are increasingly used for patients with end-stage heart failure, the need for noncardiac surgical procedures (NCSs) in these patients will continue to rise. We examined the various types of NCS required and its outcomes in LVAD patients requiring NCS. The National Inpatient Sample Database was examined for all patients implanted with an LVAD from 2007 to 2010. Patients requiring NCS after LVAD implantation were compared to all other patients receiving an LVAD. There were 1, 397 patients undergoing LVAD implantation. Of these, 298 (21.3%) required 459 NCS after LVAD implantation. There were 153 (33.3%) general surgery procedures, with abdominal/bowel procedures (n = 76, 16.6%) being most common. Thoracic (n = 141, 30.7%) and vascular (n = 140, 30.5%) procedures were also common. Patients requiring NCS developed more wound infections (9.1 vs . 4.6%, p = 0.004), greater bleeding complications (44.0 vs . 24.8%, p < 0.001) and were more likely to develop any complication (87.2 vs . 82.0%, p = 0.001). On multivariate analysis, the requirement of NCSs (odds ratio: 1.45, 95% confidence interval: 0.95–2.20, p = 0.08) was not associated with mortality. Noncardiac surgical procedures are commonly required after LVAD implantation, and the incidence of complications after NCS is high. This suggests that patients undergoing even low-risk NCS should be cared at centers with treating surgeons and LVAD specialists.